Perancangan Basis Data Inventaris dan Transaksi pada Reda Printing Berbasis Single Admin - Andhika Galang Adisaputro; Ignatius Gavrilla Reda; Diaz Kahfi Baldan; Zatin Niqotaini (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
Reda Printing is a printing business that still relies on manual recording for raw material inventory and operational transactions. This condition causes various issues, such as stock mismatches, sudden depletion of production materials, and the absence of a structured transaction track record, which ultimately burdens the management that relies heavily on a single administrator. This study presents the design of an integrated relational database system to address these problems. The design was carried out through three main stages: Entity Relationship Diagram (ERD) for logical modeling, Conceptual Data Model (CDM) as a conceptual representation, and Physical Data Model (PDM) for technical implementation. This system integrates five core entities—Barang, Supplier, Transaksi_Masuk, Order, and Detail_Order—which are implemented into MySQL. The added value of this design is the application of database-level automation using Triggers and Views, which function to update stock automatically and provide early warnings (smart alerts) when stock reaches its minimum limit. The results of this database design are expected to serve as the foundation for developing a reliable, accurate, and efficient operational information system to support Reda Printing's productivity.